1997
DOI: 10.1055/s-2007-979528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypericum Extract (LI 160) in Biochemical Models of Antidepressant Activity

Abstract: Since the mechanism of the antidepressant activity of hypericum extract is not yet understood, we tested possible effects of standardized hypericum extract (LI 160) in several biochemical models relevant for the mechanism of action of other antidepressant drugs. While LI 160 was only a weak inhibitor of MAO-A and MAO-B activity, it inhibited the synaptosomal uptake of serotonin, dopamine and norepinephrine with about equal affinity-2 micrograms/ml). Moreover, subchronic treatment of rats with hypericum extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
166
0
5

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(182 citation statements)
references
References 8 publications
11
166
0
5
Order By: Relevance
“…18 Hypericum's potency on monoamine re-uptake inhibition is remarkable as previous studies by the same authors have shown that classical antidepressants such as imipramine were also active in these systems with IC 50 values around 20 nmol L −1 for the 5-HT and NA uptake systems. 17 Comparable potencies were also found in the literature for other antidepressants (Table 2). More recently Neary and Bu 21 reported the first study on the effects of hypericum on 5-HT and NA transport in intact neuronal cells.…”
Section: Experimental Pharmacology Of Hypericumsupporting
confidence: 59%
See 3 more Smart Citations
“…18 Hypericum's potency on monoamine re-uptake inhibition is remarkable as previous studies by the same authors have shown that classical antidepressants such as imipramine were also active in these systems with IC 50 values around 20 nmol L −1 for the 5-HT and NA uptake systems. 17 Comparable potencies were also found in the literature for other antidepressants (Table 2). More recently Neary and Bu 21 reported the first study on the effects of hypericum on 5-HT and NA transport in intact neuronal cells.…”
Section: Experimental Pharmacology Of Hypericumsupporting
confidence: 59%
“…[24][25][26] Quercetin and Quercitrin, both flavonoide aglykone constituents of hypericum extract have also been shown to inhibit MAO-A, 27 although a therapeutic action of these compounds remains questionable because of their low plasma levels. Supporting the negative findings, studies by Muller et al 17 showed that the IC 50 values of hypericum as an inhibitor of MAO-A or MAO-B activity exceeded 100 g ml −1 (100 times higher than the IC 50 for inhibition of monoamine re-uptake), making it unlikely that both these mechanisms are involved in the antidepressant action of hypericum. However the effect of hypericum on MAO-A and MAO-B inhibition may be dose-related as a study by Kako et al 28 suggests that extremely high doses of hypericum are needed to actively inhibit MAO.…”
Section: Experimental Pharmacology Of Hypericummentioning
confidence: 93%
See 2 more Smart Citations
“…The pharmacological activity of SJW extracts has recently been reviewed (Butterweck, 2003;Greeson et al, 2001;Nathan, 1999). Reports about the antidepressant activity of SJW extracts and their constituents both in vivo and in vitro have been published (Baureithel et al, 1997;Butterweck et al, 1997Butterweck et al, , 1998Butterweck et al, , 2000Butterweck et al, , 2001aButterweck et al, , b, 2002Calapai et al, 1999;Chatterjee et al, 1996Chatterjee et al, , 1998aDi Matteo et al, 2000;Franklin and Cowen, 2001;Gobbi et al, 1999Gobbi et al, , 2001Müller et al, 1997Müller et al, , 1998Müller et al, , 2001Simmen et al, 1999Simmen et al, , 2001Singer et al, 1999;Wonnemann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%